A floating microbial fuel cell: Generating electricity from Japanese rice washing wastewater. (December 2020) - Nguyen, Dang-Trang; Taguchi, Kozo
Abstract: Microbial fuel cells (MFCs) are a green technology that can directly convert electrical energy from chemical energy contained in organic wastewater. Rice is the most popularly consumed food in Asia. Rice washing before cooking produces an enormous amount of domestic sewage. Rice washing wastewater (RWW) contains various organic matters, minerals, and vitamins. Therefore, in this study, we utilized RWW as biofuel to operate a floating MFC (FMFC). The FMFC was designed with the air-cathode floating on the biofuel and the anode immersed in the biofuel. This design enables the device to float on wastewater sources and to harvest electricity directly from that source. Baker's yeast and bacteria existing in a natural pond (natural bacteria) were used as biocatalysts. Experimental results showed that the FMFC could generate electricity from RWW using both the baker's yeast and natural bacteria. The maximum power density ow the FMFC using the baker's yeast was 1 mW/m 2 .